Morenci Hyrometallurgical Process Improvement - Application Of Six Sigma In Process Improvement - R. Blosser (Canadian Institute of Mining, Metallurgy and Petroleum, 2007)
Phelps Dodge introduced a process improvement model known as Quest for Zero in 2001. In 2004, the focus of Quest for Zero shifted from corporate-led initiatives to projects led by site personnel. The Hydrometallurgical Division at Morenci focused on two (2) significant process improvements: reducing electrolyte bleed and organic losses. In September 2004, Morenci kicked off a bleed reduction project to reduce electrolyte bleed by 45%. By the end 2005, electrolyte bleed was reduced by 55% through understanding and reduction of variance. Significant process changes made during this time period include changes in acid-addition strategy, reduction of uncontrolled bleed, and optimization of bleed placement. In April 2005, the organic reduction project began with the goal of reducing losses by 15%. Operational improvements during this project included improved organic recovery systems, mixer speed optimization, and picket fence installation. By the end 2005, this project reduced organic losses by 35% and current losses are 48% lower than at the start of the project. These projects and smaller Questfor Zero projects have resulted in sustainable annualized savings of $13 million in Morenci hydrometallurgical operations. Through the use of Six Sigma tools, process variances can be controlled and reduced.